A Parametric study on the effects of winglet cant angle on wing aerodynamics and aeroacoustics - Erfan Vaezi; S. Amirreza S. Madani; Amir Keshmiri (Scientific Reports)
Abstract The use of winglet devices is an efficient technique for enhancing aerodynamic performance. This study investigates the effects of winglet cant angles on both the aerodynamics and aeroacoustics of a commercial wing, comparing them to other significant parameters using a parametric analysis. A Full Factorial Design method is employed to generate a matrix of experiments, facilitating a detailed exploration of flow physics, with lift-to-drag ratio (L/D) and the integral of Acoustic Power Level (APL) as the primary representatives of aerodynamic and acoustic performance, respectively. The RANS formulation, along with the $$k{-}ε$$ Realizable model and the Broadband Noise Source (BNS) model, are utilized to accurately simulate subsonic flows numerically. The study begins by examining the pressure coefficient ( $$C_p$$ ) and APL distributions at various cant angles near the wingtip and root areas. The matrix of experiments is then analyzed to identify the most influential parameters based on the main effects of inputs and their two-way interactions. The results demonstrate that variations in winglet cant angle significantly alter the distribution of $$C_p$$ and APL along the span, particularly near the wingtip, and that cant angle strongly impacts overall performance, at times even outweighing atmospheric parameters such as pressure and temperature.